READINESS IN FACING DISASTERS ON INDONESIAN PEOPLE - Rinaldi Rinaldi (Jurnal Psikologi, 2009)
Indonesia is located in The Pasific Ring of Fire or in the circle of active fire mountains in the earth. As a result, the volcanic activity and its underground eruption cause a lot of earthquakes which is followed by tsunami. Earthquake and tsunami caused thousand people die and a lot of people lost their wealth. Unfortunately, Indonesian people are still weak in case of preparation from disaster. In other words, disaster preparation in this discussion refers to the ability and awareness of Indonesian people to save their lives when disaster comes. However, preparation itself can be devided into simulation, survival training and guidance in order to avoid building’s crash. As a result, it increasing the ability of residents to survive from disaster. Furthermore, the characteristics of disaster contains of rescue preparation, the competence to struggle, plaining and recovering. Meanwhile, dimension of survival can also be differ into: (1) rescue information, (2) synchronize coordinate management, (3) formal and informal organinization, (4) Rescue team whose prepared to run their duty during emergency time, (5) survival recovering, (6) wealth recovering, (7) main function during emergency and recovering times and (8) recovering activity. Finally, the preparation gives awareness and belief among communities to rescue from disaster. Moreover, it help to minimize sufferer and its psychological impact.Keywords ; preparation from disaster